Functional capacity and quality of life in older women practicing and not practicing hydrogymnastics - Daniel Vicentini de Oliveira; José Roberto Andrade do Nascimento Júnior; Maria do Carmo Correia de Lima; Daniel Eduardo da Cunha Leme; Mateus Dias Antunes; Sônia Maria Marques Gomes Bertolini (Rev Rene)
Objective: to compare the functional capacity and quality of life of older women practicing and not practicing hydrogymnastics. Methods: this is a simple natural experiment study, of a sample of 40 older women practicing hydrogymnastics and 40 not practicing hydrogymnastics. Latin American Development Group’s protocol was used to evaluate the functional capacity, and the WHOQOL-Bref and Old was used to evaluate the quality of life.Results: there were no differences in functional capacity or quality of life between the groups.Conclusion: it is concluded that there was not enough strong evidence to prove that older women practicing hydrogymnastics have a different functional capacity and quality of life compared to those not practicing physical exercise.